1992
DOI: 10.1126/science.1589772
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency network oscillation in the hippocampus

Abstract: Pyramidal cells in the CA1 hippocampal region displayed transient network oscillations (200 hertz) during behavioral immobility, consummatory behaviors, and slow-wave sleep. Simultaneous, multisite recordings revealed temporal and spatial coherence of neuronal activity during population oscillations. Participating pyramidal cells discharged at a rate lower than the frequency of the population oscillation, and their action potentials were phase locked to the negative phase of the simultaneously recorded oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

52
849
1
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,080 publications
(931 citation statements)
references
References 33 publications
52
849
1
9
Order By: Relevance
“…Spontaneous mesiotemporal ripple oscillations have been described in the CA1 (Buzsáki et al, 1992), CA3, subiculum and enthorinal cortex (Chrobak and Buzsáki, 1996;Csicsvari et al, 1999) of normal rat hippocampus during episodes of awake immobility and slow-wave sleep, probably involved in information processing and consolidation of memory (Buzsaki, 1996;Siapas and Wilson, 1998). Physiological HFOs occur also in normal neocortex.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous mesiotemporal ripple oscillations have been described in the CA1 (Buzsáki et al, 1992), CA3, subiculum and enthorinal cortex (Chrobak and Buzsáki, 1996;Csicsvari et al, 1999) of normal rat hippocampus during episodes of awake immobility and slow-wave sleep, probably involved in information processing and consolidation of memory (Buzsaki, 1996;Siapas and Wilson, 1998). Physiological HFOs occur also in normal neocortex.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond this observation, it was also shown that γ oscillations may operate as a general mechanism that is capable of binding together, by a process of phase synchronization, not only the firing of neurons at the local level, but also neural activities of spatially separate cortical areas (Roelfsema et al, 1997). Furthermore, the discovery of hippocampal ripples during behavioral immobility, consummatory behaviors and slow-wave sleep (Buzsáki et al, 1992), kindled the interest for understanding the functional significance of HFOs in the process of memory consolidation. The subsequent finding that similar short transient oscillations, named "fast ripples", can be observed in the local field potential recorded from the hippocampus and the temporal cortex of epileptic humans and rodents (Bragin et al, 1999b) stimulated the interest for these oscillatory phenomena as possible biomarkers of epileptogenic neural networks.…”
Section: Introductionmentioning
confidence: 98%
“…Ripples have been thought to be more physiological in nature and involved in memory, while FRs appear to be pathological, except for FRs in sensory evoked potentials (Axmacher et al, 2008;Buzsaki et al, 1992;Curio et al, 1997;Engel et al, 2009;Worrell et al, 2008). HFOs often co-occur with epileptic spikes, but there are HFOs without spikes and spikes without HFOs (Jacobs et al, 2008;Urrestarazu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%